1992
DOI: 10.1038/ki.1992.394
|View full text |Cite
|
Sign up to set email alerts
|

Arginase is a major pathway of L-arginine metabolism in nephritic glomeruli

Abstract: L-arginine can be metabolized to nitric oxide (NO) by nitric oxide synthase (NOS) and to urea and L-ornithine by arginase. Competition between these pathways for L-arginine in inflammatory sites has been suggested. In experimental glomerulonephritis glomeruli produce nitrite; a major source is macrophages. We hypothesized that arginase is present in glomeruli and may compete for substrate with NOS in glomerulonephritis. Therefore we examined both pathways in isolated nephritic glomeruli and peritoneal macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 16 publications
3
27
0
Order By: Relevance
“…These findings will allow us to evaluate the potential use of iNOS inhibitors in the management of renal damage. A role for iNOS in mediating glomerular damage in models of renal inflammation has also been reported (Cattell et al, 1990;Cook & Sullivan, 1991;Jansen et al, 1992). A weaker protective effect was observed with the non-selective cNOS/iNOS inhibitor L-NMMA or L-NAME.…”
Section: Discussionmentioning
confidence: 83%
“…These findings will allow us to evaluate the potential use of iNOS inhibitors in the management of renal damage. A role for iNOS in mediating glomerular damage in models of renal inflammation has also been reported (Cattell et al, 1990;Cook & Sullivan, 1991;Jansen et al, 1992). A weaker protective effect was observed with the non-selective cNOS/iNOS inhibitor L-NMMA or L-NAME.…”
Section: Discussionmentioning
confidence: 83%
“…If this inhibition would occur also in lung arginase, a decreased formation of NO and citrulline would not only limit arginine availability, but also would limit inhibition of arginase, therefore channeling arginine toward urea and ornithine. There is evidence in recent investigations that in some pathophysiologic states, such as glomerulonephritis (45) and wound healing (46), there is a temporal expression of these two different pathways of L-arginine metabolism (Larginine+ornithine pathway and the L -a r g i n i n e j N 0 -citrulline pathway), depending on the pathophysiologic state. We speculate that, although it is possible that the etiology of pulmonary vasoconstriction and remodeling of the pulmonary arteries is perhaps multifactorial, involving growth factors (47), endothelins (48), and nitric oxide (4), a preferential direction of arginine metabolism toward the formation of ornithine and polyamines resulting in smooth muscle proliferation and remodeling of the pulmonary arteries, with a concomitant fall in the activity of the L-arginine-NO-citrulline pathway leading to pulmonary vasoconstriction and hypertension, may contribute to this pathology (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated arginase activity could limit NO synthesis by reducing L-arginine availability for NOS (17). It has been documented that arginase activity is 5-fold greater than NOS activity and arginase was found to be present in the major pathway of L-arginine metabolism in nephritic glomeruli (18); likewise, it was suggested that while arginase activity increases, NOS activity decreases in the erythrocytes of the patients with chronic renal failure (19). It was also reported that for the mammalian arginase, the Km for …”
Section: Discussionmentioning
confidence: 99%